Harmful algae : (UNESCO, 1998)
Harmful algal blooms are one of the consequences of the human impact on aquatic ecosystems, particularly the process of eutrophication. They can cause a variety of deleterious effects, including the poisoning of fish and shellfish, habitat disruptions for many organisms, water discolouration, beach fouling, and even toxic effects for humans. This book is a comprehensive synthesis of the latest research achievements concerning harmful algae (HA) ecology. International experts provide an in-depth analysis of HA topics including: global distribution, ecology of major HA groups, ecology and physiology of HA, HA and the food web, studying and mitigating HA, the human impact on HA and HA impact on human activity.